Life Experience of Women with Breast Cancer Undergoing Chemotherapy at Jayapura General Hospital, Indonesia - Suselo; Sri Manianti Irnawan; Siti Patimah (Sriwijaya Journal of Surgery, 2023)
Introduction: Breast cancer is the second most common cancer in the world and is the most common cancer among women. Cancer is a term used for malignant tumors, which are tumors that grow rapidly, infiltrate surrounding tissues, metastasize, and can cause death if they don't get proper treatment and therapy. One of the treatments for cancer is chemotherapy; the negative effects of chemotherapy treatment for patients can affect life. This study aimed to find out in depth the life experiences of women with breast cancer undergoing chemotherapy. Methods: The research design used is qualitative research using a phenomenological approach. The technique used is purposive sampling, with a total of 10 participants. This research was carried out at the Jayapura General Hospital in April 2023 using the in-depth interview method. Results: Subjects felt the side effects during chemotherapy, the impact during chemotherapy, adapting to reduce physical changes after chemotherapy, the support received during chemotherapy, and expectations of chemotherapy. Conclusion: Chemotherapy provides hope for patients but also causes uncomfortable side effects for patients. Efforts to educate and strengthen chemotherapy patients are important.